Dampak Kemenangan Taliban atas Afghanistan terhadap Kegiatan Terorisme di Indonesia - Muttamimah, Dewi Kamal (Department of International Relations, Brawijaya University, 2022)
The Taliban won their victory back on August 15, 2021, after its reign in the American invasion after 9/11. Where at the time, the Taliban moved Osama bin Laden from Sudan to Afghanistan and refused to turn him over to US. It is certainly of concern to the world, especially Indonesia, which is predominantly Muslim, as the Taliban aim to establish an Islamic state. Indonesia, with its long history of terrorism, should be more concerned about what the Taliban's victory will do to terrorism in Indonesia. In this article, I am trying to examine the history of the Taliban and its connections to terrorist networks in Indonesia. The Taliban's victory is concerned that it will affect the long term with humanitarian intervention following an ideological shift and trying to change state systems. As for the short term, there is the recruitment of many members of terrorist networks by giving public opinion that a Taliban victory is an Islamic victory. Keywords: terrorism, Taliban, Afghanistan, Indonesia, Islam